Physiological Studies on Growth and Reproduction of Sclerotinia sclerotiorum Causing White Rot on Eggplants under Laboratories Conditions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was aimed A series of laboratory experiments were carried out, including the study of the physiological characteristics of the Sclerotinia sclerotiorum, especially the effect of type of medium, temperature, acidity and saline concentrations on the growth of the pathogen and on its production capability on reproductive structures (sclerotia).Results showed that the type of media had a significant effect (0.05) on growth average of S. sclerotiorum and on its ability to produce sclerotia. The growth of the fungus was significantly higher in Moringa oleifera leaves medium (Mo), but substantially decreased in Petroselinum crispum (Pc) compared to that in PDA. In contrast, the formation of sclerotia substantially decreased in Pc medium (4 sclerotia/ plate) followed by Mo (7 sclerotia/ plate) compared with PDA (25 plate / plate). The highest rate of growth of S. sclerotoirum was at 20 oC on the seventh day after inoculation, followed by growth at 25 oC  and at 15 oC followed by 30 oC and the lowest growth was at 35 oC. It was found that the optimum pH for growth of S. sclerotiorum was at 5.5, but when pH increased to 4.5 the production of sclerotia was minimized to 44%. Also, the increasing of alkalinity to 8% resulted in a decrease of fungal growth to about 84% compared to the growth at  pH = 5.5.Salt concentrations (4%, 6%, and 8%) were revealed inhibitory effect on sclerotia production by S. sclerotiorum, but this effect negatively correlated with increasing concentration of NaCl. The results also showed a reduction in their production and deformity in their shaps at 4% concentration. After this concentration, fungus failed to produce the sclerotia. It can be concluded that this study highlighted the epidemiological components of the disease, which lie mainly in the application of the disease management strategy.